2005
DOI: 10.1088/0957-0233/16/5/018
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of moisture content of alfalfa using density-independent functions of microwave dielectric properties

Abstract: The use of density-independent functions of the dielectric properties of chopped alfalfa, calculated from microwave reflection coefficients from 300 MHz to 18 GHz, was studied for determining moisture content in the range from 12% to 73%, wet basis, at bulk densities from 0.139 to 0.716 g cm−3 at 20 °C. Prediction of moisture content with worst-case relative errors of about 3% or less over the range from 20% to 73% confirmed promising prospects for use of such density-independent functions for reliable moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Additionally, Ulaby and El‐Rayes (1987) found that the bound water content increases with decreasing total water content. A number of authors developed mixing models for specific purposes or vegetation compartments, such as the dielectric model for leaves as proposed by Mätzler (1994), and for various plants, such as Shrestha et al (2005, 2007).…”
Section: Canopy Dielectric and Plant Water Propertiesmentioning
confidence: 99%
“…Additionally, Ulaby and El‐Rayes (1987) found that the bound water content increases with decreasing total water content. A number of authors developed mixing models for specific purposes or vegetation compartments, such as the dielectric model for leaves as proposed by Mätzler (1994), and for various plants, such as Shrestha et al (2005, 2007).…”
Section: Canopy Dielectric and Plant Water Propertiesmentioning
confidence: 99%
“…Research studies were also published dealing with the prediction of moisture content based on microwave dielectric spectroscopy for several food items, including alfalfa [ 35 ], onions [ 36 ], dry cured ham [ 28 ], chicken and scallops [ 33 ], among others. Taking into account that the reflected TDR data were correlated with the moisture content of octopus, a calibration of this methodology was further performed to allow a rapid and accurate quantitation of moisture content in O. vulgaris .…”
Section: Resultsmentioning
confidence: 99%
“…The moisture content can be estimated by the following equation: Moisture content (g/100 g) = −0.503 × PC1 + 1.602 × PC2 + 85. 35 The root mean squared error (RMSE) between the reference moisture content (obtained with the destructive method) and the moisture content predicted by the principal component regression calibration was 1.1%, and the coefficient of determination R 2 was 0.784 (p < 0.05).…”
Section: Quantitation Of Moisture Content Of Octopusmentioning
confidence: 95%
“…On many events empirical per se calibration rules need to be applied to a class of specific materials [516][517][518][519][520], aiming, of course, at a unified description of an as broad as possible variety of species within such class [521,522]. In this context, particular interest is directed toward density-independent relations [522][523][524][525][526]…”
Section: Mixture Relationsmentioning
confidence: 99%